2020
DOI: 10.1177/1087724x20969164
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Actions to Control and Mitigate the Effects of the COVID-19 Pandemic on Construction Organizations: Preliminary Findings

Abstract: Construction organizations face many challenges in coping with the effects of the COVID-19 pandemic on the economy and the construction work environment. Although each organization is implementing its own strategies to mitigate this pandemic’s impact on operations and workers, the construction industry as a whole urgently needs to identify the most effective strategies for mitigating the effects of COVID-19 on its operations in the short term while preparing response plans and long-term recovery plans. This ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 1 publication
3
54
0
1
Order By: Relevance
“…Construction organisations must regularly monitor for public health and government announcements to ensure compliance with the most recent regulations and guidelines (Raoufi and Fayek, 2020). Okoye et al (2016) reported that compliance to safety regulations and policies is not widespread within the industry, which is consistent with the finding of this study: "Workers were restricted from eating together.…”
Section: Approach To Managing the Risk Of Covid-19 On Sitesupporting
confidence: 78%
See 1 more Smart Citation
“…Construction organisations must regularly monitor for public health and government announcements to ensure compliance with the most recent regulations and guidelines (Raoufi and Fayek, 2020). Okoye et al (2016) reported that compliance to safety regulations and policies is not widespread within the industry, which is consistent with the finding of this study: "Workers were restricted from eating together.…”
Section: Approach To Managing the Risk Of Covid-19 On Sitesupporting
confidence: 78%
“…A construction organisation insists on refusing sick workers' entrance to the site. The practice is consistent with the recommendations of Raoufi and Fayek (2020), Simpeh and Amoah (2021), which indicate that anyone who shows symptoms of COVID should be identified and disallowed from entering the site to mitigate the risk of a possible spread of the virus. The measure of requesting that workers with symptoms stay home can, however, be supported by necessary follow-ups to establish the nature of the sickness through the COVID-19 test.…”
Section: Approach To Managing the Risk Of Covid-19 On Sitesupporting
confidence: 69%
“…Emergent coding was used to identify themes and ideas within the data transcribed from the interviews [34]. Furthermore, multiple studies have already applied qualitative research methods to explore the influence of COVID-19 in the construction industry, and as such, emphasizing the value of applying these research methods to better understand the influence of the current pandemic context in the construction sector (e.g., [6,16,29]).…”
Section: Qualitative Content Analysis and Correspondence Analysismentioning
confidence: 99%
“…Similarly, Ref. [29] identified that a measure to minimize the impact on the construction supply chain is to identify at-risk suppliers that might not be replaced. Ultimately, regarding impacts on owners and public agencies, the literature indicates that workforce reduction due to the pandemic context may limit their capacity to develop new construction projects (owners) and oversee permits for construction projects in the case of agencies [11].…”
Section: Introductionmentioning
confidence: 99%
“…The results include the identification of (1) the current effects of COVID-19 on construction organizations; (2) the top actions to control and mitigate effects of the COVID-19 pandemic on construction organizations; and (3) a comparative analysis of the actions implemented in the early versus middle stages of the pandemic. A preliminary data analysis of the early pandemic survey data was presented by Raoufi and Fayek (2020). The current paper provides a complete data analysis of both the early pandemic and midpandemic survey data and also provides a comparison of different actions taken during different stages of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%